POLA KONSUMSI DAN STATUS ANEMIA REMAJA PUTRI SMA PERKOTAAN DAN PEDESAN DI KABUPATEN JEMBER - Betty Kurniawati; Farida Wahyu Ningtyias (Fakultas Kesehatan Masyarakat, Universitas Jember, 2007)
Insufficiency ferrum anaemia still be one of the inclusive major nutritional problem in Indonesia. This Analytic research Survey performed to learn the correlation between food pattern and anaemia status. Interview was executed at 125 adolescent women. Subjects were identified from population by simple random sampling method. The data gathered was analysed using chi square test on α = 0,05. It was found that the anamia prevalence was 17.6% and for the food pattern, egg and meat are most iron source which consumption with respondent. The respondent rarely consumption Fe and vitamin C supplementation. For level of consumption, there was protein and fat had sufficient dietary intake, unless energy. Statistical analysis showed that food pattern are Fe and vitamin C supplementation, meats products and vegetables diet, level of consumption of energy, protein and fat had not correlation with anamia status in both rural and urban area. Key word : Food pattern, anamia status